The effect of using teacher feedback on concept mastery and students’ self-assessment of the essay test on monohybrid and dihybrid cross topic - Allyany Hasyaty; Siti Sriyati; Amprasto Amprasto (Assimilation: Indonesian Journal of Biology Education, 2023)
This study aims to identify the effect of using teacher feedback on students' concept mastery and self-assessment on the topic of monohybrid and dihybrid crosses. The method used in this research was a quantitative quasi-experiment with Nonequivalent Control Group research design. The participants in this study were among 69 ninth grade students (33 control class students and 36 experimental class students) at one of the public junior high schools in Bandung Regency. This study uses positive written feedback with the types of supporting, direct corrective and guidance on students' essay test answer sheets. To measure students' mastery of concepts, an essay test was used with a total of 10 questions. To measure students' self-assessment, a 1-4 Likert scale questionnaire was used using indicators that were adjusted to the indicators on the essay questions. The results showed that there is a significant difference in students' concept mastery and students' self-assessment ability in the control class and experimental class. As for the N-Gain test, the category of concept mastery improvement in the control class belongs to the low criteria (0.19) and the experimental class belongs to the medium criteria (0.57). Students' self-assessment skills in the control class (60%) and experimental class (70%) are classified in the sufficient and good categories. Students' responses to the teacher’s feedback showed a positive response. Based on this research, the use of teacher feedback on essay tests affects students' concept mastery and self-assessment.